Magang atau Pekerja? Menggugat Status Abu-Abu Tenaga Paruh Waktu Mahasiswa di Fakultas Hukum UGM - Krisna Putri, Patricia Nerissa; Wijaya, Markus Togar (Jurnal Hukum & Pembangunan, 2026)
This study highlights the controversy surrounding the change in nomenclature for student workers at Gadjah Mada University, particularly within the Faculty of Law. The status of these workers has shifted from 'part-time' to 'student intern'. This unilateral change has created a legal grey area that could lead to students being subjected to disguised employment practices. Using socio-legal research methods, this article examines the validity of the 'internship' status based on the elements of an employment relationship (work, orders and wages) within the labour law regime, analysing it using the theory of structural injustice. The research findings suggest that reclassifying part-time students as interns is inaccurate as this would contradict the following regulations: Pertor 18/2016, Permendikbudristek 63/2024, and Permenaker 6/2020. Furthermore, an examination of four dimensions —power relations, procedural, distribution and legitimacy— has also revealed the fulfilment of the perspective of structural injustice.